2008
DOI: 10.1590/s1414-81452008000400016
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho das competências obstétricas na admissão e evolução do trabalho de parto: atuação do profissional de saúde

Abstract: O objetivo deste estudo foi identificar os profissionais de saúde e suas competências no atendimento às parturientes no momento de admissão na maternidade e durante a evolução do trabalho de parto e discutir as competências da equipe de enfermagem nesse atendimento. Foi realizado nas duas maternidades de Rio Branco-AC. A coleta de dados foi realizada em julho de 2005, por meio de observações das competências essenciais em obstetrícia desenvolvidas pelos profissionais de saúde. A estatística descritiva e o test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
(8 reference statements)
0
5
0
1
Order By: Relevance
“…In order to follow the advances of technology and the transformations in the society, as well as to develop strategies that promote the improvement of the developed activities, it is necessary to meet the health users' needs and improve the teams' working in a critical and reflexive matter in a professional scope. 11,12 We observed that of the seven nursing techniques, 05 always worked in the SA. Among the technical assistances were in the OC, 01 has been working for approximately 1 year and the other for 4 years.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In order to follow the advances of technology and the transformations in the society, as well as to develop strategies that promote the improvement of the developed activities, it is necessary to meet the health users' needs and improve the teams' working in a critical and reflexive matter in a professional scope. 11,12 We observed that of the seven nursing techniques, 05 always worked in the SA. Among the technical assistances were in the OC, 01 has been working for approximately 1 year and the other for 4 years.…”
Section: Resultsmentioning
confidence: 88%
“…12 On the other hand, it can be seen that nursing practice in a hospital is characterized by long working hours (night work, shifts), generating a physical and mental overload (stress). 11 Considering the data collected, two categories of analysis emerged, as entitled: "Perception on the reception with risk classification" and "Advantages of implanting the reception with risk classification sector to assist pregnant women in labor".…”
Section: Resultsmentioning
confidence: 99%
“…All subjects studied are female with ages ranging from 38 to 50 years old. Regarding education, all nurses (5) have one or more specializations, 77.7% report being married and the remainder are divorced.…”
Section: Resultsmentioning
confidence: 99%
“…This becomes a negative factor for care quality, as it leads the practitioner to use unnecessary interventions rather than practices based on scientific evidence. [5][6][7] The personal and institutional barriers faced by nursing staff members prevent qualified care. This fact evidences the need for a better investment not only in the training, but also in the permanent qualification of these professionals, as well as in the reorganization of the services so that there is incorporation of assistance protocols, in order to improve the quality in the service to the target population.⁷…”
Section: Introductionmentioning
confidence: 99%
“…These skills lead the health professional to a clinical reasoning and, consequently, the decision-making process about conducts to adopt. [22][23][24][29][30][31] However, despite the accumulation of technical knowledge, health professionals are still using actions advised against by evidences for delivery tracking such as: installation of routine intravenous infusions upon the parturient's admission, prescription and control of the acceleration of labor with oxytocin, guidance for "pushes" when the dilation is complete or nearly complete, and the use of the lithotomic position, with or without the use of leg support, for natural childbirth. 16,32 Such practices lead the woman to be subjected to pre-established conducts in assistance protocols in services that control the evolution of her labor and delivery.…”
Section: [] That They Really See the Real Conditions Of The Mothermentioning
confidence: 99%